2016
DOI: 10.1007/s11270-016-2951-7
|View full text |Cite
|
Sign up to set email alerts
|

The Removal of Bisphenol A in Water Treatment Plant Using Ultrafiltration Membrane System

Abstract: Bisphenol A (BPA) is one of the recalcitrant contaminants that are detected in drinking water sources, as the conventional water treatment plant is incapable of removing it completely. This study was conducted to explore the performance of ultrafiltration (UF) membrane system for the BPA removal in which BPA was spiked in water sample collected from a treatment plant. The effects of process conditions that may influence the removal and flux performance of the membrane including operating pressure, feed pH and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The physical modification significantly influences the further process of ROS generation. We rationalize that the conventional thermodynamics of the bubble collapse phenomenon led to ozone breakdown. Furthermore, this process comprises three sequential stages, namely, initiation, propagation, and termination.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The physical modification significantly influences the further process of ROS generation. We rationalize that the conventional thermodynamics of the bubble collapse phenomenon led to ozone breakdown. Furthermore, this process comprises three sequential stages, namely, initiation, propagation, and termination.…”
Section: Resultsmentioning
confidence: 80%
“…Thus, in this study, the experimental fouling process of ceramic membranes was not a focus. The flux of the fouled membrane was measured at 608 L/h/m 2 by using the flux test instrument for the cross-flow membrane 26 depicted in Figure 2 . A distribution pump facilitated the circulation of water throughout the system.…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that the yields achieved in the c-UF system without the self-cleaning system did not exceed 15-25%. This is mainly because ultrafiltration processes are not the most effective for removing dissolved organic material [37,69]. When the self-cleaning system is included, it did not bring with it a significant reduction since the small observed improvement of 2.6% was within the range of experimental error.…”
Section: Effect Of the Self-cleaning System On The Water Qualitymentioning
confidence: 98%
“…It proved to be an effective barrier for the removal of viruses and bacteria, suspended solids, parasites and microorganisms. [31,[33][34][35][36][37] Biological Conventional Active sludge systems, despite being the most widely used in WWTP, were the least efficient for removing complex mixtures of CECs due to the specific biodegradability of each contaminant. In a WWTP in Finland, they obtained a CEC removal efficiency of 26% for diclofenac while for naproxen an efficiency close to 97-100%.…”
Section: Physical Adsorptionmentioning
confidence: 99%
“…Despite its reputation as one of the most harmful pollutants, BPA is necessary in the industrial production of epoxy resins and polycarbonate polymers. BPA is a white crystalline substance (powder or flake) with a slight phenolic odor that can be found in the environment [1]. Food containers, plastic bottles, toys, water pipes, medical equipment, dental products, electronic devices, compact discs, thermal paper, vehicle parts, and adhesives have all been found to contain BPA [1].…”
Section: Introductionmentioning
confidence: 99%